Lime Soap as Bacteria Reducer - Ratih Dewi Dwiyanti; Leka Lutpiatina (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2018)
Some people in South Kalimantan have used river water to fulfill their daily needs include washing the utensils. Wash the cutlery use river water can cause disease transmission. Squeezed lime has an antibacterial effect in inhibiting bacterial growth. Antibacterial dishwashing soap is effective in reducing pathogenic bacteria. This research is to know the difference of bacterial amount on the variation of contact time with soap. Know the difference of bacteria on the variation of concentration of lime soap and soap without lime. The study used the experimental method with pretest and posttest with control design. The independent variables are a lime soap with a concentration of 40%, 50%, 60% and variable of contact time 30 second, 60 second and 90 seconds. The dependent variable is the number of bacteria on the dinnerware of a dinner plate. The data obtained in this study is the data of measurement of the number of bacteria on the dinner plate. Data analyzed by Kruskal-Wallis test. MPN coliform examination of river water showed results >2400 CFU/ml sample. There were no significant differences in treatment with contact time variation of 30 seconds, 60 seconds and 90 seconds. The significance value is 0.796 (> 0.05). There were significant differences in the treatment of lime soap with concentration variations of 40%, 50%, 60%, and soap without lime. The value of significance is 0,000 (<0.05).